Tiempos fundacionales : nación, identidades y prácticas discursivas en las letras latinoamericanas - Kottow, Andrea; Massmann, Stefanie (Universidad Andrés Bello : RiL editores, 2015)
The articles in this book reflect on the culture of nineteenth-century Latin America and examine the significance of literature.